Social capital, parental expectation, and postsecondary education enrolment - Wahyu Wisnu Utomo (Economic Journal of Emerging Markets, 2017)
In this research paper, I attempt to investigate the correlation between parental expectation and postsecondary education enrolment in Indonesia. Not only parental expectation, I also aim to shed a light in higher educational attainment topic by examine the correlation between social capital and the enrolment decision because the studies that connecting parental expectation and social capital to postsecondary education enrolment were not many, especially in Indonesia. Using fourth and fifth wave of IFLS (Indonesia Family Life Survey) in 2007/2008 and 2014/2015, I find that parental expectation has a positive connection with the postsecondary education enrolment. In addition to that, two community participation variables from the dataset that I use to measure social capital also shows a significant relationship. Furthermore, the logistic regression also shows that age, marriage status, gender, ethnicity, religion, student’s academic capacity, parent’s education, wealth, and location are significant determinants. I also find interesting results that in Indonesia, girls are more likely to participate in postsecondary education compared to boys, and early marriage is the biggest obstacle to the higher education enrollment.